Effect of corn supplementation on the expression of intramuscular fat genes. - Coria, M.S. (2020)
Objective. The aim of the present study was to determine the effect of supplementing pasture-finished Braford steers with corn silage on the expression level of genes associated with intramuscular fat in longissimus dorsi muscle. Materials and methods. Thirty Braford steers grazing on summer pasture were used for the study. For 120 days fifteen animals were supplemented with corn silage at 1% of body weight per head per day (Supl) whereas the remaining 15 steers only received pasture (Cont). Animals were slaughtered at 26 month of age with 464±17 Kg. Gene expression of glucose transporter type 4 (glut4), insulin-like growth factor 1 (igf1) and myostatin were measured using real-time polymerase chain reaction (RT-qPCR). Results. Supplementation produced increased expression of glut4 and igf1 genes. The expression of the genes studied was correlated with hot carcass weight, fat score of carcass and intramuscular fat content. Conclusions. Results suggest a gene expression-diet interaction in glut4 and igf1 genes, which impact on carcass fattening and intramuscular fat content in longissimus dorsi muscle of Braford steers, suggesting that these meat variables could be modulated through differential gene expression.